2009
DOI: 10.1007/s12088-009-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a hyperactive nitrile hydratase from resting cells of Rhodococcus rhodochrous PA-34

Abstract: A propionitrile-induced nitrile hydratase (NHase), a promising biocatalyst for synthesis of organic amides has been purifi ed from cell-free extract of Rhodococcus rhodochrous PA-34. About 11-fold purifi cation of NHase was achieved with 52% yield. The SDS-PAGE of the purifi ed enzyme revealed that it consisted of two subunits of 25.04 kD and 30.6 kD. However, the molecular weight of holoenzyme was speculated to be 86 kD by native-PAGE. This NHase exhibited maximum activity at pH 8.0 and temperature 40°C. Half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Since this is a heterodimeric enzyme, the elevated temperature may adversely affect enzyme stability, causing the two subunits to dissociate. Generally, the nitrile hydratases of mesophilic bacteria exhibit maximum activity at ambient temperatures between 20 and 40°C (59). Pseudomonas sp.…”
Section: -H-e-g-r-c-f-v-vmentioning
confidence: 99%
“…Since this is a heterodimeric enzyme, the elevated temperature may adversely affect enzyme stability, causing the two subunits to dissociate. Generally, the nitrile hydratases of mesophilic bacteria exhibit maximum activity at ambient temperatures between 20 and 40°C (59). Pseudomonas sp.…”
Section: -H-e-g-r-c-f-v-vmentioning
confidence: 99%
“…by producing surfactant on hydrophobic substrate demonstrated high resistance towards cell lysing. There is even a published report previously stating that protein extraction using ultrasonification method of Rhodococcus strain seems to be less effective due to high rigidity and odd chemical composition of the cell membrane (Prasad et al 2009). Considering these, a comparison study to determine effective cell lysing method was esteemed to be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…The specific activity of RZ44 nitrilase was about 616 and 1383 U.mg -1 for acetonitrile and acetamide, respectively. The specific activities for R. rhodochrous J1 (115 U.mg -1 dcw) (17), R. pyridinovorans MW3 (97 U.mg -1 dcw) (46), B. imperialis CBS 498-74 (47 U.mg -1 dcw) (47), and R. rhodochrous PA-34 (55.0 U.mg -1 dcw) (25) have been reported. These results indicated that RZ44 has high substrate tolerance and higher nitrilase activity.…”
Section: Discussionmentioning
confidence: 99%